Integrated New Approach Methods Using Zebrafish (Danio rerio) Larvae and Transcriptomics Produce Points of Departure that are Protective of Chronic Toxicity Effects - Curry, Jory (Université d'Ottawa / University of Ottawa, 2023)
There is growing concern that current toxicological test methods are too slow and expensive to evaluate the safety of the thousands of chemicals in the Canadian economy. In this thesis, a novel zebrafish embryo test, with integrated behaviour, energy expenditure and gene transcription assays, was used to assess the hazard of a diverse suite of 29 chemicals. I hypothesized that points of departure (PODs) from the integrated test would be protective of the long-term toxic effects of these chemicals. I found that: 1) integrating alternative test methods enhanced the sensitivity of the zebrafish embryo acute toxicity (FET) test, 2) integrated results provided a holistic understanding of potential mechanisms of action and effects, and 3) transcriptional PODs were protective of PODs from traditional long-term and short-term juvenile and adult fish toxicity tests reported in the literature. This integrated zebrafish embryo test is a sensitive, informative and protective chemical hazard screening tool.
Keywords: Transcriptomics; Point of Departure; Ecotoxicology; Toxicology; Bioinformatics; Dose Response; New Approach Methods; Concentration response; Integrated approaches to testing and assessment; chemical risk assessment